Michavilla, F. y Calvo, B. (2000) La Universidad Española hacia Europa. Madrid: Fundación Alfonso Martín Escudero. 287 páginas - Isabel Cantón Mayo (Universidad de La Rioja, 2013)
Michavilla, F. y Calvo, B. (2000) La Universidad Española hacia Europa. Madrid: Fundación Alfonso Martín Escudero. 287 páginas.